Penerapan Metode Diskusi dalam Meningkatkan Pemahaman Pembelajaran PAI di Kelas XI SMA Negeri 1 Tambun Selatan - Sugiyantoro; Ghofur, Abdul (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The core purpose of this method is as a form of solving a problem, answering problems and understanding students' knowledge, as well as making decisions. Therefore, discussion is not a debate involving argumentation. But discussions are more like exchanging experiences to justify certain decisions together. The type of research used in this study is field research with a qualitative approach, namely research used to study the conditions of natural objects (as opposed to experiments) where the observer is the key instrument. The data collection procedures used were interviews and observation. From the results obtained in the learning process using the discussion method, learning using the discussion method really helps students' learning. And there are no more students playing with friends, daydreaming, sleeping, chatting with friends, or playing alone.